Application of textile (PAN-based) activated carbon fibers decorated with silver nanoparticles in water treatment - Martins, Isabela M. [UNESP]; Sampaio, Aline G. [UNESP]; Lima, Gabriela M. G. [UNESP]; Oliveira e Campos, Maria A. C. [UNESP]; Rodgher, Suzelei [UNESP]; Rodrigues-Siqueli, Aline C.; Baldan, Maurício R.; Marcuzzo, Jossano S.; Koga-Ito, Cristiane Y. [UNESP] (Frontiers, 2023)
Introduction: Water treatment deficit and poor health, hygiene and sanitation infrastructure can contribute to disease transmission by dissemination of contaminants and microorganisms. As an alternative, carbon-based materials coated with antimicrobial molecules have been proposed for water treatment, but few supporting data are available so far. Hence, this study investigates the potential use of PAN-based activated carbon fibers (ACF) decorated with silver nanoparticles in water treatment. Methods: Silver nanoparticles were incorporated into the material using a cheap and electroless method. Field emission scanning electron microscopy (FEGSEM), Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) characterized the whole material. The textile was mounted on a water filter prototype and had its capacity to remove bacterial (Escherichia coli) and fungal (Candida albicans, Aspergillus niger and Penicillium funiculosum) cells evaluated. Composition and toxicity of the filtered water were determined. Results: Water filtered by Ag@ACF for 2 and 24 h contained 0.254 mg/L and 0.964 mg/L Ag, respectively. Ag@ACF filtering successfully removed E. coli, C. albicans, and A. niger from the suspensions, but not P. funiculosum. Treated water was non-toxic for Vero cells and Drosophila melanogaster, but toxic for Raphidocelis subcapitata. Ag@ACF showed efficient microbial elimination when applied in water treatment. Silver nanoparticles released in aqueous medium may be responsible for R. subcapitata toxicity. Future studies should be conducted to reduce silver nanoparticles release from the carbon fiber.
Keywords: antimicrobial effect; decontamination; silver nanoparticles; toxicity; water treatment